Character, Audience Agency and Trans-Media Drama - Evans, Elizabeth (Sage, 2007)
Changes in the television industry with regards to the development of new media technologies are having a significant impact on audience engagement with television drama. This article explores how the internet is being used to extend audience engagement onto platforms other than the television set to the point where television drama should increasingly be reconsidered as trans-media drama. However audience engagement with the various elements of a trans-media drama text is complex. By exploring audience attitudes towards character in the British television series Spooks and its associated online games, this article argues that in an increasingly converged media landscape audiences transfer values between platforms. Consequently the audience's perception of control in relation to their engagement with a trans-media drama text such as Spooks becomes complicated with values associated with television proving key to their engagement with the same fictional world in the form of games.